2018
DOI: 10.1016/j.ccell.2018.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Ezh2 and Runx1 Mutations Collaborate to Initiate Lympho-Myeloid Leukemia in Early Thymic Progenitors

Abstract: Lympho-myeloid restricted early thymic progenitors (ETPs) are postulated to be the cell of origin for ETP leukemias, a therapy-resistant leukemia associated with frequent co-occurrence of EZH2 and RUNX1 inactivating mutations, and constitutively activating signaling pathway mutations. In a mouse model, we demonstrate that Ezh2 and Runx1 inactivation targeted to early lymphoid progenitors causes a marked expansion of pre-leukemic ETPs, showing transcriptional signatures characteristic of ETP leukemia. Addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 48 publications
6
50
0
2
Order By: Relevance
“…In addition, increased EZH2 expression is also associated with tumor progression and poor prognosis of glioma, wherein both genetic and pharmacological EZH2 inhibition eradicate self-renewal and tumorigenicity of GSCs 131 , 142 , 143 . Additionally, EZH2 loss in combination with JAK2 V617F, RUNX1, TET2, or NRas G12D mutations can initiate myeloid or lymphoid malignancies 144 - 148 . Both gain- and loss-of-function PRC2 mutations can be tumorigenic 149 , 150 , indicating that chromatin remodeling factors drive cancer initiation and progression in a context-dependent manner.…”
Section: Chromatin Remodeling In Cscsmentioning
confidence: 99%
“…In addition, increased EZH2 expression is also associated with tumor progression and poor prognosis of glioma, wherein both genetic and pharmacological EZH2 inhibition eradicate self-renewal and tumorigenicity of GSCs 131 , 142 , 143 . Additionally, EZH2 loss in combination with JAK2 V617F, RUNX1, TET2, or NRas G12D mutations can initiate myeloid or lymphoid malignancies 144 - 148 . Both gain- and loss-of-function PRC2 mutations can be tumorigenic 149 , 150 , indicating that chromatin remodeling factors drive cancer initiation and progression in a context-dependent manner.…”
Section: Chromatin Remodeling In Cscsmentioning
confidence: 99%
“…Another study conducted by Booth et al focused on inactivation of EZH2 and RUNX1 in progenitor rather than stem cells and found that combined inactivation enhances proliferation of early thymic progenitors in mice. Additional RAS-signaling pathway activation in form of an internal tandem duplication of Fms Related Receptor Tyrosine Kinase 3 (FLT3-ITD), frequently detected in AML and associated with a worse prognosis, resulted in aggressive lympho-myeloid leukemia [62]. EZH2 mutations also frequently co-occur with TET2 mutations [47,48,60].…”
Section: Mutual Exclusion and Concomitance Of Ezh2 And Other Leukemiamentioning
confidence: 99%
“…[21][22][23], suggesting that PRC2 regulates normal HSCs in a dose-dependent manner. Although studies have shown that Ezh2 loss in combination with other lesions such as Jak2 V617F , Runx1, or Tet2 mutations promote myeloid or lymphoid malignancies (24)(25)(26)(27)(28), it remains unclear how different PRC2 dosages contribute to the development of hematopoietic malignancies under physiologic conditions.…”
Section: Introductionmentioning
confidence: 99%